2011
DOI: 10.2174/092986711796391688
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the Human DEAD-Box Polypeptide 3 (DDX3) RNA Helicase as a Novel Strategy to Inhibit Viral Replication

Abstract: Compounds currently used for the treatment of HIV-1 Infections are targeted to viral proteins. However, the high intrinsic mutation and replication rates of HIV-1 often lead to the emergence of drug resistant strains and consequent therapeutic failure. On this basis, cellular cofactors represent attractive new targets for HIV-1 chemotherapy, since targeting a cellular factor that is required for viral replication should help to overcome the problem of viral resistance. We and others have recently reported the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 121 publications
0
37
0
1
Order By: Relevance
“…23,24), including, most recently, small molecule inhibitors that target the DDX3 RNA binding site as a potential anti-HIV therapy. 23 However, numerous studies have demonstrated that DDX3 and its yeast homolog (Ded1p) function in multiple cellular processes involved in the regulation of gene expression (reviewed in refs.…”
Section: Ddx3mentioning
confidence: 99%
“…23,24), including, most recently, small molecule inhibitors that target the DDX3 RNA binding site as a potential anti-HIV therapy. 23 However, numerous studies have demonstrated that DDX3 and its yeast homolog (Ded1p) function in multiple cellular processes involved in the regulation of gene expression (reviewed in refs.…”
Section: Ddx3mentioning
confidence: 99%
“…6C). DDX3 has recently been identified with a number of small-molecule inhibitors as a potential anti-HIV therapeutic (20,43,44,55). Therefore, the identification of DDX3 as an intracellular factor required for norovirus replication provides an additional target for small-molecule intervention against norovirus infection.…”
Section: Figmentioning
confidence: 99%
“…Several inhibitors of the ATPase activity of DDX3 have been recently identified (29)(30)(31)(32)(33)(34); however, an ATP-mimetic compound may have a low degree of selectivity in vivo because of the possibility of interacting with many targets (35).…”
mentioning
confidence: 99%